PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN DEALER MOKAS SEMERU MOTOR DI MASA PANDEMI - Sani, Muhammad Mahrus; Hafidzi, Achmad Hasan; Reskiputri, Tatit Diansari (Relawan Jurnal Indonesia, 2023)
Purchasing decisions become better, namely the goal for all employees to want to achieve larger purchasing targets. The purpose of this study was to determine the effect of the marketing mix on purchasing decisions for Mokas Semeru Motor dealers during the pandemic. the covid-19 pandemic has greatly affected the level of sales of Mokas Semeru. We can see the sales data in May with sales of only 6 units of motorbikes because in that month the Covid-19 pandemic was endemic, especially in Jember Regency plus in May it collided with the month of Ramadan so that people are more concerned with daily needs than complementary needs like a motorcycle. The population used in this study were all consumers of Mokas Semeru Motor Dealers. The sample used was 125 respondents, using a non-probability sampling technique. The data analysis technique uses multiple linear regression analysis. The results of this study indicate that the Marketing Mix variable has a significant effect on purchasing decisions during a pandemic. Shows a good and appropriate assessment of the indicators Mokas Semeru Dealers offer used motorcycle products at prices that are in accordance with the condition of the unit, Mokas Semeru Dealers offer used motorcycle products according to market prices, and Mokas Semeru Dealers offer used motorcycle products at affordable prices. The suggestion in this study is for mokas dealers to increase marketing towards purchasing decisions during a pandemic. The variables in this study explain the frequency distribution of respondents' answers about the indicators contained in this research questionnaire statement, namely Product (X1), Price (X2), Place (X3), Promotion (X4), HR (X5), Process (X6 ), Physical Evidence (X7), and Purchase Decision (Y). The scores given by respondents to each statement in the questionnaire reflect how they perceive the research variables.